2016
DOI: 10.18632/oncotarget.14221
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient-induced FNIP degradation by SCFβ-TRCP regulates FLCN complex localization and promotes renal cancer progression

Abstract: Folliculin-interacting protein 1 and 2 (FNIP1 and FNIP2) play critical roles in preventing renal malignancy through their association with the tumor suppressor FLCN. Mutations in FLCN are associated with Birt-Hogg-Dubé (BHD) syndrome, a rare disorder with increased risk of renal cancer. Recent studies indicated that FNIP1/FNIP2 double knockout mice display enlarged polycystic kidneys and renal carcinoma, which phenocopies FLCN knockout mice, suggesting that these two proteins function together to suppress rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 57 publications
(93 reference statements)
1
12
0
Order By: Relevance
“…In contrast, mTORC1 regulation was unperturbed in Flcn KO ESCs. Although unexpected, Flcn-and Fnip1/2-independent mTORC1 activation in response to aas has been described before in other cell types (Nagashima et al, 2017;Wada et al, 2016). We conclude that GATOR-dependent regulation of RagA/B mediates mTORC1 activation by aas but not differentiation of non-starved ESCs.…”
Section: Non-canonical Raggtpase Regulation and Signaling In Escssupporting
confidence: 69%
See 1 more Smart Citation
“…In contrast, mTORC1 regulation was unperturbed in Flcn KO ESCs. Although unexpected, Flcn-and Fnip1/2-independent mTORC1 activation in response to aas has been described before in other cell types (Nagashima et al, 2017;Wada et al, 2016). We conclude that GATOR-dependent regulation of RagA/B mediates mTORC1 activation by aas but not differentiation of non-starved ESCs.…”
Section: Non-canonical Raggtpase Regulation and Signaling In Escssupporting
confidence: 69%
“…We surmise that independent regulation of Tfe3 and mTORC1 in ESCs allows differential control of ESC proliferation (Gangloff et al, 2004;Murakami et al, 2004), exit from self-renewal, and translation (Sampath et al, 2008) in response to intra-and extracellular cues. Lysosome activity, Flcn-Fnip, and Tsc, which are all directly associated with cellular nutrition (Nagashima et al, 2017;Saxton and Sabatini, 2017), inactivate RagC/D and Tfe3 in ESCs. It is therefore conceivable that the quantitative and qualitative integration of multiple nutritional signals forms a metabolic differentiation checkpoint that anticipates energy requirements faced during developmental progression.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with a model in which Flcn/Fnip inhibits mTORC1 activation, in contrast with the siRNA knockdown studies outlined previously. One potential mechanism for how Flcn/Fnip might alter mTORC1 activation was proposed by Nagashima et al ., who found that ubiquitination and degradation of Fnip2 under fed conditions led to lysosomal dissociation of FLCN and subsequent constitutive lysosomal association of mTOR irrespective of nutrient status [56] (Figure 3). Overall, these studies highlight the complexity of the mTORC1 signaling pathway in response to Flcn/Fnip, and indicate that the control of mTORC1 by the Flcn/Fnip complex is highly dependent on the nutritional state and the type of cells studied.…”
Section: Overview Of Mtor Signaling Pathwaysmentioning
confidence: 99%
“…FLCN binds to two partner proteins, FLCN-interacting proteins 1 (FNIP1) and 2 (FNIP2). The interaction between FLCN and FNIP1/ FNIP2 is a critical element for the FLCN/FNIP1/FNIP2 complex to exert tumor suppressive functions and to control energy homeostasis by regulating PGC1a-driven mitochondrial oxidative metabolism (15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%